Efektivitas Badan Keuangan dan Aset Daerah (BKAD) terhadap Pengawasan Barang Milik Daerah Kabupaten Lebak - Heri Susanto; Firdaus Firdaus; Danial Danial (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2022)
Management of regional property areas that are increasingly developing and complex needs to be supported by comprehensive arrangements adapted to developing needs so that the planning, implementation, and supervision processes can be managed optimally, effectively, and efficiently. Two problems need to be discussed and analyzed. First, what is the function of the Supervision of the Regional Finance and Assets Agency (BKAD) on the security of regional property in terms of Law Number 1 of 2004 concerning the State Treasury? Second, how is the implementation of Law Number 1 of 2004 concerning the State Treasury 1 of 2004? Whether the State Treasury can guarantee the Protection and Security of Regional Property. The research was conducted in a qualitative descriptive analysis with a normative juridical approach. The research sources used consisted of primary data and secondary data. The legal materials used in this study consist of primary legal materials, secondary legal materials, and tertiary legal materials. Data collection techniques were carried out in a documentary and interview. The results show that the Regional Finance and Assets Agency (BKAD) Supervision Function on the Security of Regional Property in Law Number 1 of 2004 concerning the State Treasury has been implemented by the Regional Finance and Assets Agency. Belonging to the region in the form of securing building land; Security of buildings and/or buildings; Security of official vehicles; Statehouse security; Security of supplies; Security other than building land and buildings; Security of intangible goods. The Implementation of Law No. 1 of 2004 concerning the State Treasury can guarantee the Protection and Security of Regional Property following the Supervision Function of the Regional Financial and Assets Agency (BKAD) on the Security of Regional Property